Information design on medicine inserts: analysis and classification of the structure and graphic presentation of its textual content - Fujita, Patricia Lopes; Spinillo, Carla Galvão (InfoDesign, 2010)
This paper approaches the medicine insert on the perspective of information design. Some theoretical references are presented, in order to justify the medicine insert as an essential document in the use of medicines and the need of its investigation. Moreover, aspects about the medicine insert’s textual structure and graphic presentation were discussed. In concern to the textual structure, are presented the textual function of the medicine insert defined by Marshall (1984) and its superstructure classification according to van Dijk (1992). The graphic presentation is discussed taking into account the graphic aspects in the communication efficacy and the graphic-informational deficiencies that make difficult its reading and comprehension.